2020
DOI: 10.1002/er.5782
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the performance advantage of using passive solar air heater with chimney for photovoltaic module cooling

Abstract: Summary The foreseeable growth of photovoltaic (PV) systems highlights the prominence of improving its efficiency. The performance of PV module deteriorates as a major part of irradiance is converted to heat. Amongst several PV thermal management techniques, passive air cooling is gaining importance due to its self‐sustained nature. In the present experimental study, the performance of conventional solar air heater is enhanced by incorporating chimney. Further, by placing the PV module in the airflow path, its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Zheng et al [33] designed a system aimed at reducing the working temperature of solar photovoltaic panels, which effectively improved their operational efficiency. On the other hand, Chandrasekar et al [34] reported a technique that used passive thermal regulation in the form of fins combined with cotton wicks. This technique was employed to control the temperature of the photovoltaic (PV) module during operation.…”
Section: Passive Coolingmentioning
confidence: 99%
See 1 more Smart Citation
“…Zheng et al [33] designed a system aimed at reducing the working temperature of solar photovoltaic panels, which effectively improved their operational efficiency. On the other hand, Chandrasekar et al [34] reported a technique that used passive thermal regulation in the form of fins combined with cotton wicks. This technique was employed to control the temperature of the photovoltaic (PV) module during operation.…”
Section: Passive Coolingmentioning
confidence: 99%
“…Overall, there have been important advances in optimizing the cooling efficiency of solar photovoltaic panels. These include integrated systems converting solar to electrical energy [27], lapping fins [28], cotton core structures integrated with nanofluids [29], water-based hybrid PV/T systems [30], the use of slits [31], container-based systems [32], and passive thermal regulation techniques [33,34]. Each method has its own unique attributes, but all share the common goal of improving PV panel cooling efficiency and, thus, their operational efficacy.…”
Section: Passive Coolingmentioning
confidence: 99%
“…The research of combined systems also shows diversification: the combination of multiple systems to maximize energy saving. Chandavar [63] explored the effectiveness of coupling the solar chimney and PV modules by field tests. As two self-sustained systems, the two components complement each other in their work, thus improving thermal efficiency.…”
Section: Potential Trends and Challenges Of The Solar Chimneymentioning
confidence: 99%